The Impact of Supply Chain Capabilities on the Performance of Food Industry in Thailand - Kittisak Jermsittiparsert; Samanan Wattanapongphasuk; Somsathid Phonwattana (International Journal of Supply Chain Management, 2019)
This study investigates the impact of the capabilities of supply chain management on the performance of the food industry in Thailand. Data were collected from the mangers of the supply chain of the firm that are listed in the Department of Industrial Work Thailand by distributing the survey through the mail. PLS-SEM has been used to test the links between the variables under study. The results of the multiple regressions revealed that effective SCM capabilities could increase the performance of the firm. Results highlighted that supply chain integration, supply chain operations and human resource management are significantly related to business performance. The SCM of the food industry of Thailand has that type of effective capabilities that enhance the performance of the business.